Analyzing the Spirituality of Muslim Experiential Religiousness: Relationships with Psychological Measures of Islamic Religiousness in Iran. (May 2013) - Ghorbani, Nima; Watson, P.J.; Geranmayepour, Shiva; Chen, Zhuo
This investigation analyzed Islamic spirituality as measured by a Muslim Experiential Religiousness Scale. Iranian university and seminary students (N = 351) responded to this instrument along with the Psychological Measure of Islamic Religiousness (PMIR) and Perceived Stress and Self-Esteem scales. Muslim Experiential Religiousness correlated predictably with all PMIR sub-scales, Perceived Stress, and Self-Esteem, and mediated almost all relationships of the PMIR Islamic Beliefs subscale with religious functioning. When evaluated by participants, Muslim Experiential Religiousness items proved to be "rational" relative to their Muslim religious ideals. Women in an Islamic seminary scored higher on Muslim Experiential Religiousness than Islamic women in a more general university, and Muslim Experiential Religiousness also mediated the many other religious differences observed between these two student groups. These data most importantly identified the Muslim Experiential Religiousness Scale as a useful instrument for testing hypotheses about the dynamics of Muslim spirituality.